Web-age information management : WAIM 2013 International Workshops: HardBD, MDSP, BigEM, TMSN, LQPM, BDMS, Beidaihe, China, June 14-16, 2013. Proceedings - Xiao, Yingyuan; Liu, An; Qiao, Shaojie; Gao, Yunjun (Lecture Notes in Computer Science, 2013)
This book constitutes the refereed proceedings of six workshops of the 14th International Conference on Web-Age Information Management, WAIM 2013, held in Beidaihe, China, June 2013. The 37 revised full papers are organized in topical sections on the six following workshops: The International Workshop on Big Data Management on Emerging Hardware (HardBD 2013), the Second International Workshop on Massive Data Storage and Processing (MDSP 2013), the First International Workshop on Emergency Management in Big Data Age (BigEM 2013), the International Workshop on Trajectory Mining in Social Networks (TMSN 2013), the First International Workshop on Location-based Query Processing in Mobile Environments (LQPM 2013), and the First International Workshop on Big Data Management and Service (BDMS 2013).